Watts-level super-compact narrow-linewidth Tm-doped silica all-fiber laser near 1707 nm with fiber Bragg gratings. (30th September 2016) - Xiao, X S; Guo, H T; Lu, M; Yan, Z J; Wang, H S; Wang, Y S; Xu, Y T; Gao, C X; Cui, X X; Guo, Q; Peng, B
Abstract: Watts-level ultra-short wavelength operation of a Tm-doped all fiber laser was developed by using a 1550 nm Er-doped fiber laser pump source and a pair of fiber Bragg gratings (FBGs). The laser yielded 1.28 W of continuous-wave output at 1707.01 nm with a narrow linewidth of 44 pm by means of a 20 cm Tm-doped fiber. The dependencies of the slope efficiencies and pump threshold of the Tm-doped fiber laser versus the length of active fiber and reflectivity of the output mirror (FBG) were investigated in detail, in which the maximum average slope efficiency was 36.1%. There is no doubt that this all fiber laser will be a perfect pump source for mid-IR laser output.